Monitoring to reduce agency costs: Examining the behavior of independent and non-independent boards - Anita Anand; Frank Milne; Lynnette Purda (Queen's University, Department of Economics, 2010)
Berle and Means's analysis of the corporation - in particular, their view that those in control are not the owners of the corporation - raises questions about actions that corporations take to counter concerns regarding management's influence. What mechanisms, if any, do corporations implement to balance the distribution of power in the corporation? To address this question, we analyze boards of directors' propensity to voluntarily adopt recommended corporate governance practices. Because board independence is one way to enhance shareholders' ability to monitor management, we probe whether firms with independent boards of directors (which we define as boards with either an independent chair or a majority of independent directors) are more likely than firms without independent boards to adopt these practices. We focus on boards' willingness to monitor their firms' agents, examining the relationship between board independence and the voluntary adoption of corporate governance guidelines.
Keywords: D0; G0; K0; L0; 330; Corporate Governance; Agency Costs; Monitoring; Independent Boards; Corporate Governance; Eigentümer; Führungskräfte; Kontrolle; Leistungsanreiz; Unternehmenserfolg